후천성면역결핍증후군 환자에게 급성 호산구성 폐렴 양상을 보인 폐포자충 폐렴 1예 - 이보라; 김현국; 박이내; 최상봉; 정훈; 이현경; 이성순; 이영민; 이혁표; 최수전; 염호기; Lee, Bo-Ra; et al. (Tuberculosis and respiratory diseases, 2010)
A 73-year-old man was admitted with a sudden onset of dyspnea. He had never smoked. The chest radiograph and computed tomography revealed bilateral ground glass opacity and an enlarging perihilar consolidation with lymphadenopathies. There was a higher percentage of eosinophils (72%) in the bronchoalveolar lavage fluid (BALF) than normal. The patient was diagnosed with acute eosinophilic pneumonia and managed with steroid. Pneumocystis pneumonia (PCP) was diagnosed by an examination of the BALF, and the patient was treated with trimethoprim-sulphamethoxazole. The patient tested positive to the HIV antibody and the peripheral blood CD-4 positive lymphocyte count was only $33/μL$. The percentage of eosinophils in the BALF can increase in some cases of PCP that is complicated with AIDS. Only a few cases of eosinophilic pneumonia associated with PCP pneumonia have been reported in patients with AIDS but there are no case reports in Korea. This case highlights the need to consider PCP when the percentage of eosinophils in the BALF is elevated.